2016
DOI: 10.2147/opth.s117494
|View full text |Cite
|
Sign up to set email alerts
|

The measurement repeatability using different partition methods of intraretinal tomographic thickness maps in healthy human subjects

Abstract: PurposeTo determine the repeatability and profiles with different partition methods in intraretinal thickness layers in healthy human subjects, using optical coherence tomography (OCT).MethodsA custom-built ultrahigh-resolution OCT was used to acquire three-dimensional volume of the macula in 20 healthy subjects. The dataset was acquired twice using the macular cube 512×128 protocol in an area of 6×6 mm2 centered on the fovea. Commercially available segmentation software (Orion™) was used to segment the datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…18 The macular cube was automatically segmented (Fig. 5) to obtain the total retinal thickness (TRT) and six intraretinal maps, including the RNFL, GCIPL (GCL + IPL), INL, OPL, ONL, and photoreceptor complex (PR).…”
Section: Methodsmentioning
confidence: 99%
“…18 The macular cube was automatically segmented (Fig. 5) to obtain the total retinal thickness (TRT) and six intraretinal maps, including the RNFL, GCIPL (GCL + IPL), INL, OPL, ONL, and photoreceptor complex (PR).…”
Section: Methodsmentioning
confidence: 99%
“…As described previously, 16,17,20 the custom UHR-OCT system is a spectral domain OCT with an axial resolution of~3 lm in tissue and a scan speed of 24,000 A-scans per second. The scan pattern was a raster scan with 512 A-scans (per B-scan) 3 128 B-scans, which covered a field of view of 6 3 6 mm centered on the fovea.…”
Section: Topographic Thickness Maps Of Intraretinal Layers Using Ultrmentioning
confidence: 99%
“…The scan data set was exported and segmented using an automatic image processing software program (Orion, Voxeleron LLC, Pleasanton, CA, USA). 17 Segmentation of all intraretinal layers of the horizontal scan (fast scan) and the vertical scan (slow scan) crossing the foveal center, and the thickness map of the total retina were exported and saved as a record for segmentation verification. However, the segmentation of each Bscan was not checked.…”
Section: Topographic Thickness Maps Of Intraretinal Layers Using Ultrmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, automated segmentation software programmes that enable analysis layers of the retina qualitatively and quantitatively have been introduced [15,16]. Using these softwares, recent studies of AMD eyes have demonstrated that there were a change not only in the outer retinal layers as previously established but also in the inner retina such as the ganglion cell complex (GCC) thickness, which includes GCL and inner plexiform layer (IPL) [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%